Volatility and the welfare costs of financial market integration - Agénor, Pierre-Richard 1957-; Aizenman, Joshua 1949- (1998)
This paper examines the effect of volatility on the costs and benefits of financial market integration. The basic framework combines the costly state verification model and the contract enforceability approach. The welfare effects of financial market integration are assessed by comparing welfare under financial autarky and financial openness -- under which foreign banks, characterized by lower costs of intermediation and a lower markup rate, have free access to domestic capital markets. The analysis shows that financial integration may be welfare reducing if world interest rates under openness are highly volatile. The basic framework is then extended to consider the case of an upward-sloping domestic supply curve of funds and congestion externalities. It is shown, in particular, that opening the economy to unrestricted inflows of capital may magnify the welfare cost of existing distortions, such as congestion externalities or deposit insurance.
Keywords: Finances internationales - Modèles économétriques; Intermédiation financière - Modèles économétriques; Marché financier - Modèles économétriques; Mouvements de capitaux - Modèles économétriques; Taux d'intérêt - Modèles économétriques; Économies externes - Modèles économétriques; Ökonometrisches Modell; Capital market -- Econometric models; Capital movements -- Econometric models; Externalities (Economics) -- Econometric models; Interest rates -- Econometric models; Intermediation (Finance) -- Econometric models; International finance -- Econometric models